Study of Identification of Microplastic Waste in Sand Sediment at Lambutoa Beach, Takalar Regency - Umar, Hasdinar; Husain, Firman; Humairah, Indah Putri (Maritime Park: Journal of Maritime Technology and Society, 2023)
Indonesia is currently one of the countries in East Asia which produces around 50% of the world's coastal waste. Microplastics in Indonesian seawater range from 30 to 960 particles/liter. The purpose of this study was to determine the size, amount, type, and microplastic polymers present on Lambutoa Beach in Takalar Regency. This study uses quantitative methods to examine certain populations or samples. Quantitative research methods are used to examine populations or certain samples, data collection uses research measuring instruments, and data analysis is quantitative/statistical in nature, with the aim of testing and proving the hypotheses that have been made/defined. The stages carried out during the research process were sand sediment sampling, sand sediment sample processing, observation and identification of microplastic types, and testing using the FTIR tool. From the results of this study, it was found that there were 49 samples of microplastic waste with an average size of 1-5 mm. There are three types of microplastic contained in the sand sediments that have been tested, namely films, fragments, and foam. For the type of polymer that is most often found in testing sediment samples using the FTIR tool on microplastic samples, these are Other (Nylon) and PET (Polyethylene Terephthalate) polymers